2019
DOI: 10.1051/e3sconf/201910000083
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the flow field inside a square cyclone separator using DPIV and CFD

Abstract: This study used CFD and DPIV to investigate the flow field inside a square cyclone. For CFD, turbulent flow was modelled using 3D RANS equations (with an RSM complementary model). The results of the analysis indicate that the flow inside a square cyclone has two constituents: an outer, free flow and an inner, forced flow in the centre, as with cyclones with the traditional structure. Furthermore, the results indicate that the corners of a square cyclone generate additional vortexes that cause pressure drop to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To account for the near-wall effects, we use the standard wall function. Such numerical settings were also used by [16,[47][48][49][50].…”
Section: Mesh Generation and Solver Settingsmentioning
confidence: 99%
“…To account for the near-wall effects, we use the standard wall function. Such numerical settings were also used by [16,[47][48][49][50].…”
Section: Mesh Generation and Solver Settingsmentioning
confidence: 99%
“…These parameters collectively define the physical dimensions and characteristics of the cyclone, playing a pivotal role in shaping its flow pattern and governing its operational efficiency. Modification of geometric parameters, including the vortex finder's shape and size, cyclone separator configuration, diameter, inlet entry angle, and height, significantly enhanced the cyclone separator performance [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14]. Various studies, such as those by Xiong et al [15] observed that the inclusion of both reflux cone and spiral gap (15° clockwise rotation) designs in the vortex finder led to a significant 73% decrease in pressure drop, while simultaneously increasing the total separation efficiency by 9%.…”
Section: Design Of Stairmand Hementioning
confidence: 99%